TEORI PENGAKUAN DAN PENGUKURAN AKUNTANSI SYARIAH VERSUS AKUNTANSI UMUM - Hariyati, Tri Retno (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
yariah accounting and general accounting has its own characteristic in applying the accounting recognition and measurement. Accounting for the recognition and measurement of sharia grouped by type and each of its accounting treatment according to the contract/ agreement, for general accounting apply in general, in accordance with generally accepted accounting standards.General accounting have the same items with the accounting recognition of sharia in the accounting, as for the item that is a burden, obligation, asset, income, where different treatment. To sharia adjusted to the type of accounting (Murabaha, Salam accounting, accounting Istishna, Mudharabah accounting, accounting Musharaka, Ijarah accounting, and accounting transactions of insurance).For general accounting measurement that is based on the size of clear historical cost, current cost, realizable value, present value is valid for financial accounting. Meanwhile, Islamic accounting treatment of transactions adjusted akadnya and types of accounting, and applies exclusively Islamic institutions.